The Possibility of Estimating the Coseismic Deformationfrom Water Level Observations in Wells - Kopylova G.N.; Steblov G.M.; Boldina S.V.; Sdelnikova I.A. (Pleiades Publishing, Ltd. (Плеадес Паблишинг, Лтд) (Род-Таун), 2010)
A method for point estimation of coseismic volume deformation from amplitudes of earthquake generated changes in the water level and from the tidal sensitivity of the water level is presented. Application of this method is illustrated by six Kamchatka earthquakes of 1997–2004 with mw = 6.2–7.8 that occurred 128–316 km from the YuZ-5 well. Estimates of coseismic deformation provided by the level gage observations and by the model agree in amplitude and sign. The model reproduces an extended dislocation source in a homogeneous elastic isotropic half-space. Source rupture parameters correspond to focal mechanisms from the CMT international catalog. Consistence in experimental and theoretical estimates of the volume coseismic deformation indicates the high strain-resistance properties of YuZ-5 borehole and the possibility of quantitative estimation of seismotectonic deformation from high-precision water level measurements with time resolution not lower than 10 minutes.
Keywords: 37.31.19 Сейсмология; 37.31.27 Земные приливы; 38.61.15 Динамика и режим подземных вод